Hungarian - Egyptian Interwar Relations - Komár, Krisztián (Études sur la Région Méditerranéenne, 2003)
My study presents the relations of the two countries concentrating on some important factors between the two World Wars, that is, more exactly, during the period from the end of the 1920s to the end of the 1930s. The lecture relies mostly on primary archives, as well as on some contemporary works. The lecture is divided into more parts. First, I wish to talk about the development of the Hungarian Foreign Service in Egypt, second, I present the political relationship between the two countries, and finally, the formation of the Hungarian-Egyptian economic and trade relations will be discussed.